The Term Castle as a Toponym of Archaeological Sites in Peru - Alvarez Vera, Alcides R. (2021)
The arrival of the Spaniards to the central Andes in the 16th century meant a change in all aspects of social life, including linguistics, which resulted in new names from Castilian for people and places. The research focuses on an analysis of the constructive lexicon used in the Peruvian colonial period, a specific case of castle, and how it derived to name pre-Hispanic sites. Based on the review of the colonial written source, characteristics of European castles and Peruvian archaeological sites with that name, we proceed to the analysis of lexical semantics. Finally, it is concluded that the similarities that served to equate archaeological sites with European castles were based on the image metaphor, since these sites had other functions.